2020
DOI: 10.3389/fphys.2020.01078
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of lncRNA and mRNA Reveals Enhanced Lipolysis Along With Metabolic Remodeling in Mice Infected With Larval Echinococcus granulosus

Abstract: Parasitic infection improves metabolic homeostasis in "western diet"-induced obesity through the regulation of adipogenesis. However, the underlying mechanism is not yet fully understood. Using microarray analysis, this study investigated the long noncoding RNA (lncRNA) and messenger RNA (mRNA) profiles of subcutaneous adipose tissues from mice infected with Echinococcus granulosus protoscoleces. A total of 1052 mRNA (541 upregulated, 511 downregulated) and 220 lncRNA (126 upregulated, 94 downregulated) transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Recent studies have confirmed that ACOD1/itaconate axis links metabolism to immunity in macrophage (123), and has gained lots of interests in immunometabolism field and inflammatory disease models (124,125). Interestingly, our microarray analysis in the fat tissues with larval E. granulosus infection also showed the upregulated levels of SUCNR1, succinodehydrogenase (SDH) and ACOD1 and enriched pathways such as Arginine metabolism and PPAR signaling pathway (67), which is consistent to the M2 polarization of macrophage post infection (Figure 1). These studies highlight the intimate interconnection between immune and metabolism of host and parasite.…”
Section: Summary and Prospectmentioning
confidence: 71%
See 2 more Smart Citations
“…Recent studies have confirmed that ACOD1/itaconate axis links metabolism to immunity in macrophage (123), and has gained lots of interests in immunometabolism field and inflammatory disease models (124,125). Interestingly, our microarray analysis in the fat tissues with larval E. granulosus infection also showed the upregulated levels of SUCNR1, succinodehydrogenase (SDH) and ACOD1 and enriched pathways such as Arginine metabolism and PPAR signaling pathway (67), which is consistent to the M2 polarization of macrophage post infection (Figure 1). These studies highlight the intimate interconnection between immune and metabolism of host and parasite.…”
Section: Summary and Prospectmentioning
confidence: 71%
“…In obese mice, M1 macrophages are accumulated, while parasitic infection often induce M2 polarization of macrophage, thereby reducing the inflammatory response ( 2 ). Lu et al showed that infection of the larval Echinococcus granulosus ( E. granulosus ) can enhance the lipolysis in the fat of mice, which accompanies with enhanced arginine metabolism and PPAR-γ pathway activation ( 67 ). It is well known that arginine metabolism is closely associated with M2 polarization.…”
Section: Macrophagementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ESPs derived from parasites can directly inhibit the differentiation of T helper 17 (Th17) cells and polarize macrophages toward the M2 phenotype ( 34 , 36 ), thereby creating an anti-inflammatory microenvironment. In addition, our latest study showed that the larval E. granulosus infection enhances lipolysis, which is accompanied by a decline in carbohydrate oxidation and an increase in fatty oxidation ( 37 ). These studies collectively suggest that larval E. granulosus and its ESPs can effectively remodel the host immunity and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the host lncRNA pro les after Echinococcus infection were mainly identi ed in Echinococcus granulosus-infected mice or cells [20][21][22]. However, the host lncRNA expression pattern and functional activities in response to Em infection are poorly investigated.…”
Section: Introductionmentioning
confidence: 99%